STUDI TENTANG IMPLEMENTASI PENDIDIKAN KARAKTER BANGSA MELALUI MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMA/ MA SEDERAJAT MUHAMMADIYAH KOTA PEKANBARU - Ronaldo, Ronaldo; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research conducted because of a lot of social variances coming through students especially SMA students. For these cases, it was necessary to commit an intensive treatment for educating the students. One of the solutions recommended was implementing nation character building in order to apply the moral values, to be able to facing the challenges in future, and live independently in globalization era. Therefore, the writer conducted a research entitling “A Study on the Implementation of Nation Character Building through Civics Education in SMA/MA Muhammadiyah Pekanbaru.” The research question in this study was ‘how good is the implementation of Nation Character Building through Civics Education in SMA/MA Muhammadiyah Pekanbaru?’ The purpose of the research is to find out how good the implementation of Nation Character Building through Civics Education in SMA/MA Muhammadiyah Pekanbaru is. The population was all the civics education teachers and the eleventh grade students of SMA/MA Muhammadiyah Pekanbaru by the total number were 8 teachers and 1024 students.  The sample was the 8 teachers and 105 students. The instrument used to collect the data was Questionnaire that consisted of 74 items of questions/statements and Interview sheet that consisted of 15 questions. The data was analyzed by using the percentage of Descriptive Qualitative. From the calculation of percentage concluded that the total answers of the respondent was Fairly Well as much of 62, 88% at the rank between 56% - 75%. According to the research finding, it could be concluded that the implementation of Nation Character Building through Civics Education in SMA/MA Muhammadiyah Pekanbaru was Fairly Well.  Key Words: Implementation, Nation Character Building, Civics Education.